Village Asset Management Policy Implementation In Galagamba Village, Ciwaringin District, Cirebon Regency - Hendri Suwarsono (Jurnal Syntax Transformation, 2024)
This study aims to analyze the management of village assets in Galagamba Village, Ciwaringin District, Regency. In the context of village development, effective asset management is essential to improve community welfare. The research method used is a combination of qualitative and quantitative approaches, with data collection through in-depth interviews, questionnaires, observation, and document analysis. The results showed that village asset management still faces various challenges, including low community participation, weak accountability, and lack of transparency in asset information management. In addition, many assets are poorly inventoried and in need of repair. The impact of this suboptimal management is seen in the social and environmental welfare of the community. Based on the findings, it is recommended to increase the capacity of human resources, open space for community participation, and apply the principle of transparency in asset management. This research provides important insights for village governments in formulating more effective and sustainable policies for village asset management in the future.